Analytical study of point fixed glass façade systems under monotonic in-plane loading. Issue 4 (April 2016) - Sivanerupan, S; Wilson, JL; Gad, EF; Lam, NTK
The point fixed glass façade system is popular and considered a more elegant façade option compared to the framed glass façade system mainly for storefront, walkways and lobby areas in buildings. Point fixed glass façade system is fixed to the support structure using special bolt fittings and structural spider arms. Generally, the racking performance of these systems is not considered at the design stage in low to moderate seismic region and the system may be vulnerable if there is insufficient in-plane drift capacity compared with the demand imposed during earthquakes and wind actions. A unique full-scale in-plane racking laboratory test on a typical point fixed glass façade system was conducted and a maximum drift of 2.1% was measured before catastrophic failure. Non-linear finite element models were then developed and benchmarked against experimental results. The experimental results and finite element analyses indicated that a significant amount of the drift capacity was attributed to the rigid body translation in the façade system connections at the built-in oversize holes provided for construction tolerances. In this article, the laboratory test setup and the experimental results are summarised, and the finite element modelling methodology and non-linear analysis approach undertaken using ANSYS for the experimental test are discussed along with number of parametric studies.